2014
DOI: 10.1152/japplphysiol.01022.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the hemodynamic and sympathetic responses at the onset of isometric handgrip exercise

Abstract: Cardiac and peripheral vasomotor factors contribute to the rapid pressor response at the onset of isometric handgrip exercise. We tested the hypothesis that age enhances the sympathetic and vasoconstrictor response at the onset of isometric handgrip exercise so that the pressor response is maintained, despite a diminished cardiac function. Twelve young and twelve older (24 ± 3 and 63 ± 8 yr) individuals performed 20-s isometric handgrip exercise at 30, 40, or 50% of maximal voluntary contraction force. Muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 26 publications
4
59
1
Order By: Relevance
“…Several studies suggest attenuated responses with aging in old (13,17,18,24,25) and middle-aged (16) adults and informed our hypothesis that the venous distension reflex would also be attenuated in middle-aged adults. However, while these exercise studies are relevant because the same skeletal muscle sensory afferents of the exercise pressor reflex are thought to mediate the venous distension reflex (33), the stimulus is very different.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Several studies suggest attenuated responses with aging in old (13,17,18,24,25) and middle-aged (16) adults and informed our hypothesis that the venous distension reflex would also be attenuated in middle-aged adults. However, while these exercise studies are relevant because the same skeletal muscle sensory afferents of the exercise pressor reflex are thought to mediate the venous distension reflex (33), the stimulus is very different.…”
Section: Discussionsupporting
confidence: 73%
“…This is despite the fact that the exercise pressor reflex is augmented in many disease states associated with aging, as previously mentioned. Lalande et al (17) performed repetitive bouts of short duration isometric handgrip exercise and found that the older adults experience sympathoinhibition rather than sympathoexcitation during low-intensity exercise. Despite this, they found that the blood pressure response is unaffected by age.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of aging on exercise-induced increases in blood pressure remain equivocal, with some studies revealing an exaggerated response in the elderly (17,18), whereas others have found no difference across age groups (24,30,32,56). Since the MAP response to both absolute and relative exercise intensities was similar in both groups (Fig.…”
Section: Aging and The Exercise Pressor Reflexmentioning
confidence: 98%
“…For example, a reduction in sympathetic vasoconstrictor neural outflow is documented at the onset of seated isometric quadriceps exercise (37) and low-intensity leg cycling (20) that may be secondary to activation of the cardiopulmonary baroreceptors resulting from an increase in venous return and right atrial pressure by the skeletal muscle pump (46,48). In contrast, sympathetic vasoconstrictor activity is typically unchanged at the onset of moderate intensity isometric handgrip and in- creases at higher handgrip intensities (26). In addition, dynamic exercise is accompanied by an increase in a plethora of released vasodilatory substances with the capacity to reduce SVR (27).…”
Section: Discussionmentioning
confidence: 99%